2013
DOI: 10.1016/j.jiph.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors related to dengue infections in primary school students: Exploring students’ basic knowledge of dengue and examining the larval indices in southern Thailand

Abstract: Risk factors for dengue were related to the students' basic knowledge of dengue and to the larval indices in both the schools and the students' households. Additionally, a coordinated effort will be required to eliminate Aedes aegypti mosquito breeding sites in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 13 publications
2
22
0
7
Order By: Relevance
“…Asimismo, aún fue más baja la proporción de conocimientos de las medidas para evitar la picadura del vector adulto. En otras regiones endémicas los escolares conocen mejor el uso de mosquiteros, repelentes comerciales o inclusive repelentes naturales (25) .…”
Section: Discussionunclassified
“…Asimismo, aún fue más baja la proporción de conocimientos de las medidas para evitar la picadura del vector adulto. En otras regiones endémicas los escolares conocen mejor el uso de mosquiteros, repelentes comerciales o inclusive repelentes naturales (25) .…”
Section: Discussionunclassified
“…This step followed the consensus of all stakeholders reached at the meeting in the assessment step. These results indicated that the high risk of dengue in primary schools was from both primary school and their householders [20]. Data feedback to the school involved discussion with the primary schools using the results from the preparation and exploration step.…”
Section: Participatory Program Development Stepmentioning
confidence: 98%
“…Results of assessment step presented 290 students (primary education level 4, 5, and 6) from five primary schools in the community. The results of this step were high risk of dengue problem because highly level of dengue indices (BI, HI, and CI) in primary schools (200, 60, and 8), and their households (754, 77, and 35) [20]. There were five questions for which more than 80% of students answered correctly such as: question number 2; 9; 10; 14 and 15 (82.5%; 84.3%; 89.2%; 95.8%; and 82.4%, respectively).…”
Section: Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…DHF is a disease caused by the dengue virus that is transmitted through the bite of the Aedes aegypti mosquito (Moektiwardoyo et al, 2014;Natalia et al, 2013). Herbal medicines has already used (Lin et al, 2014;Jain et al, 2008) to encourage the pain of hemorrhagic fever (DHF) (Suwanbamrung et al, 2013;Zunjar et al, 2016). Papaya extract is also can be used as anti DHF (Ahmad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%